1994
DOI: 10.3354/meps111265
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of inorganic and organic phosphorus compounds to natural assemblages of microorganisms m Hawaiian coastal waters

Abstract: The bioavailability of 7 organic and 2 inorganic phosphorus compounds to natural communities of coastal marine bacteria and phytoplankton was evaluated. A bioavailability factor (BF) based on changes in the turnover time of the phosphate pool (measured using 3'P0,) in the absence and presence of selected phosphorus compounds, relative to positive controls receiving PO,, was calculated as an index of the relative microbial metabolic preference for each added compound. There were marked differences in the bioava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 26 publications
5
130
2
Order By: Relevance
“…Friebele et al 1978, Berman 1983, Currie & Kalff 1984, Thingstad et al 1993, Bjorkman & Karl 1994, Dolan et al 1995). Yet, some reports point to a similar contribution of phytoplankton and bacteria (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Friebele et al 1978, Berman 1983, Currie & Kalff 1984, Thingstad et al 1993, Bjorkman & Karl 1994, Dolan et al 1995). Yet, some reports point to a similar contribution of phytoplankton and bacteria (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to phosphorus limitation, experiments conducted with a marine Synechococcus indicated that the ambient inorganic phosphorus concentration in the surface ocean of 0.5 Â 10 À9 M would be sufficient to maintain a growth rate of 1.0 d À1 (Ikeya et al, 1997). It has been demonstrated that in addition to inorganic N and P, a variety of organically bound N (Wafar et al, 1995) and P (Bjorkman and Karl, 1994;Li, 1998) is present. For both Prochlorococcus and Synechococcus (Donald et al, 1997) there is evidence that growth is optimised by enriching the media with these organic compounds.…”
Section: àmentioning
confidence: 99%
“…Small nucleotides (e.g. Adenosintriphosphat) can be easily assimilated, whereas polymers (DNA, RNA) are characterized by long turnover times, resulting in accumulation of DOP in the water column (Thingstad et al, 1993;Björkman and Karl, 1994). Consequently, the biochemical composition of the individual DOP pool determines its bioavailability and is pivotal for its removal by bacteria and microalgae.…”
Section: Effect Of Different Nutrient Enrichment On Organic Matter Pamentioning
confidence: 99%